EFEKTIVITAS PROGRAM BANTUAN PENDIDIKAN DALAM MENGURANGI PUTUS SEKOLAH DI INDONESIA: EVALUASI IMPLEMENTASI KARTU INDONESIA PINTAR - Albert, Albert; Masduki, Masduki; Rochimah, Heni (Jurnal Manajemen Pendidikan, 2025)
This study evaluates the effectiveness of the Jakarta Smart Card (KIP) program in increasing access to education and reducing dropout rates in Indonesia. A literature study and document review approach was used to analyze the program's coverage, aid distribution, and impact on school participation rates. The results show that KIP has made a positive contribution, but uneven distribution and delays in disbursement of funds hamper its effectiveness, especially in remote areas. Administrative constraints and low digital literacy are also major challenges. Recommendations focus on strengthening the data collection system, technological innovation, and improving cross-sector coordination to support the sustainability of the program. By evaluating these obstacles, it is hoped that more targeted solutions can be found. This study provides important input for improving national education policy. Increasing the effectiveness of the KIP program not only contributes to access to education but also to human resource development. This study is expected to be a reference for improving education policy and implementing similar programs in the future.